The determination of interface friction by means of vibrating table tests. Issue 6 (December 2018) - Pavanello, P.; Carrubba, P.; Moraci, N.
Abstract: This paper concerns the laboratory evaluation of dynamic friction in geosynthetic interfaces subjected to sinusoidal base motions. Tests were performed with a sliding block over a vibrating table with both a horizontal plane and an inclinable plane. The horizontal configuration is widely used because it is easier to interpret, whereas the inclined plane set-up is more complicated due to the variation in time of the normal component of the acceleration. An analytical method for interpreting the vibrating table test with the inclined plane configuration is described: for the purpose of comparison two geosynthetic interfaces were chosen, which exhibit very different behaviour from each other; one interface had a constant value of dynamic friction, whereas the second exhibited a relationship between dynamic friction and the relative speed of sliding. The tests, carried out with both the horizontal and the inclined plane configuration, showed how the mobilised friction was influenced by the kinematics of the block: at the same relative speed, the mobilised interface friction during tests with the horizontal plane was greater than that resulting from tests with the inclined plane. This difference may be ascribed to the patterns of relative motion at the interface, occurring in a single direction in the case of the inclined plane, and with a cyclic reversal of direction in the case of the horizontal plane.